PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN UTANG, KEBIJAKAN DIVIDEN TERHADAP KINERJA KEUANGAN DAN BIAYA AGENSI (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Yuni Kusuma Arumsari; Djumahir (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
This study aims to analyze and explain the effect of managerial ownership, debt policy, dividend policy on financial performance and agency costs in manufacturing companies in Indonesia. This study used quantitative methods with positivism approach. 20 research object manufacturing company. Collecting data using secondary data from annual reports and financial statements. Data were analyzed using path analysis. The analysis showed that managerial ownership, debt policy, dividend policy affect the financial performance; managerial ownership, debt policy, dividend policy, and financial performance affects the agency costs. The implication of this research is a manufacturing company needs to continue to pay attention to the shares owned by the portion of managerial control in the company, debt management and distribution of large dividends. Thirdly it will lead to improved financial performance so that conflicts of interest and agency costs will decrease. managerial ownership, debt policy, dividend policy, financial performance, agency costs